Analyzing the Alignment of Writing Materials in Bahasa Inggris Work in Progress with the Genre-Based Approach Stages - Andhika Wahyu Rustamaji; Dewi Rochsantiningsih; Kristian Adi Putra (South Sulawesi Education Development (SSED), 2025)
This study analyzed the implementation of the Genre-Based Approach (GBA) in the Bahasa Inggris Work in Progress textbook, with the aim of evaluating its effectiveness in supporting writing instruction in Indonesian senior high schools. Using qualitative content analysis, the study examined how writing tasks aligned with Cahyono’s (2012) GBA framework: Building Knowledge of the Field (BKOF), Modeling and Deconstruction of the Text (MDT), Joint Construction of the Text (JCOT), and Independent Construction of the Text (ICOT). The findings revealed that although the textbook was structured according to GBA principles, its implementation across the stages was inconsistent. BKOF and MDT were generally well-supported through vocabulary-building activities and teacher-led instruction, but JCOT lacked meaningful peer collaboration, and ICOT relied heavily on teacher intervention, which limited student autonomy. Moreover, the absence of explicit linguistic analysis in the MDT stage hindered students’ understanding of genre-specific language features.This study contributed to the field of textbook evaluation by identifying practical gaps in the design and delivery of GBA within EFL writing materials. It also offered pedagogical insights for improving GBA implementation, including the integration of peer interaction, metalinguistic instruction, and self-assessment tools to enhance student-centered learning. Future research should explore how teachers mediate these materials in classroom contexts and how students engage with genre-based instruction in practice.